VULVA HYGIENE DENGAN REBUSAN DAUN SIRIH TERHADAP PENYEMBUHAN LUKA PERINEUM IBU NIFAS - Endah Wijayanti; Supriadi Supriadi; Andi Heriyah (MMJ (Mahakam Midwifery Journal), 2023)
Abstract Maternal mortality (AKI) according to Ministry of Health Data (DEPKES) in 2018 indicates that infection in the third rank whole the world. Infection usually occurs in the postpartum mother caused by the lacerations or road injuries born either due to spontaneous rips or episiotomy. The high number of these cases was influenced by a less of understanding about the treatment of perineum wounds at home and poor knowledge of obstetric care. The use of vulva hygiene using betel leaf decoction is the latest innovation to accelerate the healing of perineum wound and prevent infection. To analyze the effectiveness of vulva hygiene with betel leaf boiled water in accelerating the healing of perineal wounds in postpartum mothers through literature studies. Data search is sourced from Google Scholar, Google Search, around 10 articles from 2010-2020. Data analysis was performed narrative and descriptive form. Resulting that vulva hygiene by using betel leaf boiled water has an effect to the perineal wound healing in postpartum mothers. The reseacrh Results based on the 10 articles which have been reviewed that vulva hygiene by using the leaf betel has a good effect on the wound healing perineum, innovation and this technique can be done at home independently or in aids among the family’s member. Keywords : Vulva Hygiene, Betel Leaves, Perineal Wounds